ANALISIS TINGKAT PENDAPATAN MASYARAKAT PENJUAL MAKANAN TRADISIONAL PECEL SEMANGGI - Ahmad Lutfi Al ansori; Arfida Boedirochminarni; Muhammad Sri Wahyudi Suliswanto (Program Studi Ekonomi Pembangunan, 2019)
This study aims to determine the level of income levels of the traditional foods pecel clover in Kendung, urban village in Benowo, Surabaya City.The data used in research is primary data obtained directly through interviews with the dealer food pecel clover where data obtained using methods and techniques of sampling in determining the respondents were 37 seller pecel clover in Kendung. urban village data analysis is the method used to know descriptive quantitative analysis, income, profits and efficiency business R/C Ratio Return Cost Ratio Kendung. pecel clover in urban village. The result of this research suggests that any Kendung. pecel clover in urban village. Average of seller pecel clover in Kendung urban village in one month gaining acceptance. Rp.11.391.673 later to net income obtained Rp.3.980.000. The business efficiency value of the R/C Ratio is 1.53. The amount of production sellers of pecel clover in urban vilage Kendung monthly 51300/portion.